An Epistemological Study of Naqli–Aqli Knowledge Integration in Islamic Boarding School Education - Khafidoh, Khafidoh; Mujiburrohman, Mujiburrohman (El-Rusyd, 2025)
This study aims to analyze the epistemology of Islamic education by highlighting the integration of naqli and aqli knowledge within the learning system of tahfidz Islamic boarding schools. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews with caregivers, teachers, and students, participant observation, and document analysis of curricula and instructional guidelines. The data were analyzed thematically using a descriptive-analytical approach. The findings indicate that the epistemology of Islamic education is constructed upon a naqli–aqli integration that is holistic, hierarchical, and contextual. This integration is manifested through Quran memorization and classical text studies, the strengthening of literacy and critical reasoning, values-based civic education grounded in Quranic principles, and the internalization of adab as an epistemic ethos. This epistemological model contributes to the development of students’ intellectual–spiritual character, the enhancement of critical and reflective thinking skills, and the strengthening of the social relevance of knowledge. These findings offer a conceptual contribution to the development of contemporary Islamic educational epistemology that emphasizes a balance between intellectual intelligence, spiritual depth, and social responsibility.